Additional Mosapride to Proton Pump Inhibitor for Gastroesophageal Reflux Disease: A Meta-Analysis - Nishizawa, Toshihiro (J Clin Med, 2020)
Background and Aim: In gastroesophageal reflux disease (GERD), the additive effect of mosapride to a proton pump inhibitor (PPI) is still controversial. This meta-analysis integrated randomized controlled trials (RCTs) in which mosapride combined with a PPI was compared with a PPI alone in GERD treatment. Methods: RCTs were systematically searched with the PubMed, Cochrane library, Web of Science, and the Igaku-Chuo-Zasshi database. We combined the data from the RCTs with a random effects model, calculated the standardized mean difference (SMD) and pooled the risk difference (RD) with 95% confidence intervals (CIs). Results: We included nine RCTs in the present meta-analysis. In the mosapride combined with PPI group, the improvement of the symptom score was significantly greater than that in the PPI alone group without significant heterogeneity (SMD: −0.28, 95% CI: −0.45 to −0.12, p = 0.0007). In the mosapride combined with PPI group, the symptom score after treatment was significantly lower than that in the PPI alone group (SMD: −0.24, 95% CI: −0.42 to −0.06, p = 0.007). Conclusions: Mosapride combined with a PPI significantly improved the reflux symptom score compared with that of PPI alone.